ANALISIS EKONOMI SEKTOR RIIL DAN SEKTOR MONETER DI INDONESIA - Dona, Elva; Aimon, Hasdi; Azhar, Zul (Jurnal Kajian Ekonomi, 2013)
ABSTRACT The purpose of this research to analyze (1) Influence of economic and lagged household consumption to consumption in Indonesia. (2) Influence of economic, interest rate and lagged investment to investment in Indonesia. (3) Influence of economic and exchange rate to export netto in Indonesia. (4) Influence of household consumption, government consumption, investment and export netto to economics in Indonesia. (5) Influence of reserve requirement, money supply and interest rate to money multiplier in Indonesia. (6) Influence of economic and interest rate to money demand in Indonesia. (7) Influence of economics, money supply, lagged inflation to inflation in Indonesia. Â The Result of this research are (1) As partial economic and lagged household consumption have significant effect to consumption in Indonesia (2) As partial economic and lagged investment has significant effect to investment in Indonesia, but interest rate has not significant effect. But as simultaneous all variable has significant effect. (3) As partial economic has significant effect to export netto in Indonesia. But exchange rate has not significant influence to export netto in Indonesia (4) As partial household consumption, government consumption and investment has significant effect to Economic in Indonesia but export netto has not significant influence to economic in Indonesia But as simultaneous all variable has significant effect. (5) As partial reserve requirement, money supply and interest rate has significant effect toÂ  money multiplier in Indonesia. (6) As partial economic has significant effect to money demand in Indonesia but interest rate has not significant influence to money demand in Indonesia. But as simultaneous all variable has significant effect. (7) As partial economics and money supply has significant effect to inflation in Indonesian but lagged inflation has not significant influence to inflation in Indonesia. But as simultaneous all variable has significant effect. Keywords: Economics, House hold Consumsptions, Government consumtion, Investment, Export netto, money supply, money multiplier, Inflation.